Evaluation of phytoremediation potential of Peltophorum pterocarpum (DC.) Heyne Leucaena leucocephala (Lam.) De Wit. and Crotolaria retusa Linn for waste oil contaminated soils - N.L. Edwin-Wosu; A Nkang (Journal of Applied Sciences and Environmental Management, 2016)
An ecological study was carried out to evaluate remediation potential of three hydrocarbon tolerant species (Peltophorum pterocarpum (DC.) Heyne, Leucaena leucocephala (Lam.) De Wit., and Crotolaria retusa Linn) of Fabaceae plant family in relation to enzyme activity for cleaning up soils contaminated with waste oil hydrocarbon. Biochemical analyses were carried out using classical standard procedures to assess the level of enzyme expression in relation to hydrocarbon index assessment in remediation performance through a holistic test of significance using the PROC ANOVA and Duncan’s New Multiple Range Test (DNMRT) procedures. Enzyme expression, oil removal and organic carbon sequestration of the species and the species treated soils showed that in pre-polluted soil foliar enzyme expression in the order Cr>Ll>Pp was high but reduction in post-polluted and post-phytoremediation soils in the order Cr>Ll>Pp. Generally, among species Peroxidase (POD) was higher in activity and expression than Polyphenoloxidase (PPO). The oil and grease recorded a lower content in the pre-pollution soil which increased in content in post-pollution with increase in pollution. However, the impact of phytoapplication has shown some significant (p<0.05) reduction in L. leucocephala soil in the order Ll<Pp<Cr but higher foliar content among the species in the order Ll>Pp>Cr at low enzyme expression in which P. pterocarpum had higher carbon content in the order Pp>Cr> Ll. The pre-pollution soil had a significantly lower carbon than post-polluted soils. The impact of phytoremediation has shown reduction in carbon content with P. pterocarpum treated soil significantly lower in content in the order Pp<Cr< Ll and higher foliar content in the order Pp>Cr> Ll. Thus by the forgoing trajectories and trend of indigenous enzymes, P. pterocarpum and L. leucocephala can thus be recommended as an integral component in any bioremediation technology package for waste oil polluted terrestrial environment.